Peningkatan Hasil Belajar Siswa dengan Menggunakan Model Inkuiri pada Pembelajaran Tematik Terpadu di Kelas V SDN 06 Lasi Mudo Kabupaten Agam - Ridha, Mhd; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This research is motivated by the low student learning outcomes in integrated thematic learning. Because the teacher has not used a learning model that is adapted to the characteristics students.This research to describe student learning outcomes by using the Inquiry model on integrated thematic learning.This research is a classroom action research (CAR) that uses quantitative and qualitative approaches which are carried out in two cycles.The research subjects were teachers and fifth grade students at SDN 06 Lasi Mudo Agam Regency with a total of 20 students.The results showed an increase in 1) The average assessment of the RPP in the first cycle 89% (good) and second cycle 94% (very good) 2) The average observation of the implementation of learning aspects of teachers in the first cycle 88% (good) and the second cycle 97 % (very good), 3) The average observation of the implementation of learning aspects of students in the first cycle was 82% (good), and the second cycle was 93% (very good), 4) The average student learning outcomes in the knowledge aspect of the first cycle was 80.2 ( B +) and cycle II 90.6 (A), 5) The average student learning outcomes in the skills aspect of the first cycle was 79 (B +) and second cycle was 87 (A). Therefore the Inquiry model can significantly improve student learning outcomes in integrated thematic learning.